(untitled) (Efficient: Indonesian Journal of Development Economics, 2025)
Following the implementation of fiscal decentralization, the Indonesian government has employed natural resource revenue-sharing funds as a mechanism to allocate revenues from the mining sector to producing areas. Nonetheless, research regarding the effects of fiscal windfall from mining at the local level in Indonesia remains scarce. This study aims to address the research gap by examining the impact of natural resource abundance through the distribution of mining revenue sharing funds on poverty on Sulawesi Island, the biggest nickel-producing and processing region in Indonesia. Analysis of panel data from 51 districts in Central Sulawesi, South Sulawesi, and Southeast Sulawesi for the period 2017-2022, utilizing the Fixed Effect estimation method, reveals that mining revenue sharing, intended to mitigate the adverse externalities of mining projects and alleviate poverty, is not statistically significant. Sub-sample analysis reveals that mining revenue sharing correlates with a rise in poverty rates in Southeast Sulawesi, indicating the presence of the resource curse phenomena. Simultaneously, the contributions of mining and industrial GRDP, the human development index, and the proportion of “Program Keluarga Harapan (PKH)” recipients affected the alleviation of poverty. This research underscores the necessity for the government to account for local fiscal capability and institutional quality in the administration of mining revenue sharing funds, while also advocating for economic diversification to enhance the welfare of local populations.